SYNTHESIS AND CHARACTERIZATION OF MULLITE-ZIRCONIA NANO PARTICLES BY SOL-GEL METHOD AS FILLER OF DENTAL COMPOSITE - Faza, Yanwar; Febrida, Renny (Universitas Baiturrahmah, 2024)
Background. Currently, researchers are working on the development of dental composite fillers that are composed of a combination of two or more inorganic materials. Objective. The study aims to synthesis mullite-zirconia using the sol-gel method and observe the influence of zirconia on the particle characteristics of the filler including the size of the diameter, distribution and charge of the filler. Methods. The design of this study is descriptive explorative. The study consisted of four sample groups: 100% mullite (M); 85% Muliite - 15% zirconia (MZ15); 80% Mullite - 20% circonia(MZ20); 75% mullites - 25% zirconía (MZ25). The mullite-zirconia filler synthesis was initiated by mixing the hydrolyzed-precursor after hydrolysis stage then were dried for 6 hours at 100 °C. The ZrO2 was mixed with the Mullite according to the prescribed ratio. The sample was then characterized using Particle size analysis and Zeta potential (HORIBA) Result. The results showed that the mullite-zirconia particle sizes decrease as the amount of zirconia added after the hydrolysis phase increases. Sample M, MZ15 and MZ20 showed polydisperse particle distribution while MZ25 showed monodispersed particle distribution. Mullite and mullite-zirconia particle loads in the range of 10-30 mV. This shows that the stability of the particle is incipient Conclusion. Nano-sized mullite-zirconia particles were successfully synthesized using sol-gel methods. Increased zirconium in the mullite-zirconia ratio decreased the diameter of the particle and particle load and resulted in a more homogeneous particle distribution